The influence of phytogenic additive on the antioxidant capacity, immunity and liver functions in stress-induced male rats - Koseli, E; Seyidoglu, N; Gurbanli, R; Aydin, C (Journal of the Hellenic Veterinary Medical Society, 2022)
Global animal feeding strategies have been modified due to several ecosystem changes that cause stress and decline in health, growth, and yields. According to the literature, natural additives have been fundamental to animal health from day to day. The present study measured changes in antioxidant status, immunity, liver functions and organ weights tested under stress conditions to determine whether dietary supplementation with phytogenic additive could provide beneficial effects. Forty-eight adult, male Sprague-Dawley rats were randomly separated into four groups; Control(C), Stress(S), Treatment(Tr), Treatment and Stress(TrS). Rats in groups Tr and TrS received phytogenic additive by adding into water (2mL/L) 5days a week for 28days. All rats were exposed to prolonged light phase conditions (18h light: 6h dark) for 14 days. Also, two chronic stresses, isolation and crowded environments, were applied to animals in the Stress and TrS groups. There was a significant decline in the oxidant status in untreated stress group, while phytogenic additive fed rats maintained a significantly higher total antioxidant status. This study also showed a significant increase in IL-4 and decrease in IFN-γ in the untreated Stress group compared to the Control group. There were increases in liver enzymes in the Stress group in comparison to the Control group. After the phytogenic treatment, there was an increase in the weight of the liver, intestine, brain and testes. In conclusion, this study showed that supplementation of phytogenic additive containing milk thistle and artichoke with choline, carnitine, vitamin E and melatonin describes the protective effects on antioxidant status, immunological parameters and liver functions under mixed stress conditions.